2015
DOI: 10.1007/s00170-015-7869-5
|View full text |Cite
|
Sign up to set email alerts
|

On tool–workpiece interactions during machining metal matrix composites: investigation of the effect of cutting speed

Abstract: Metal matrix composites (MMCs) are widely employed in many industrial applications due to their excellent strength and wear characteristics. In order to overcome the challenges faced during machining MMCs, knowledge regarding machinability of MMCs is considered to be an asset. This paper contributes to this field through development of a novel micromechanical finite element model of the process. The developed model includes simulation of all phases of MMC workpiece and is employed for investigation of the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The tool and the cutting speed were the parameters with more weight on the thrust force. The increase in the cutting speed caused a decrease in the thrust force due to the elevation of temperature, which softens the matrix, thus reducing its strength, as reported by [15]. In general, an increase in the feed rate leads to a higher thrust force associated with the elevation of the shear area, similar to the results reported by [3].…”
Section: Resultssupporting
confidence: 80%
“…The tool and the cutting speed were the parameters with more weight on the thrust force. The increase in the cutting speed caused a decrease in the thrust force due to the elevation of temperature, which softens the matrix, thus reducing its strength, as reported by [15]. In general, an increase in the feed rate leads to a higher thrust force associated with the elevation of the shear area, similar to the results reported by [3].…”
Section: Resultssupporting
confidence: 80%
“…According to previous studies on macro machining of micro-sized MMCs [13][14][15][16], addition of hard particles into matrix materials could greatly alter the cutting mechanism comparing with homogeneous materials. In fact, cutting tool edge radius is becoming one of the important factors governing the machining mechanism in micro machining process.…”
Section: Chip Formation Process Analysismentioning
confidence: 99%
“…Their research showed that the formation mechanism of machined surface defects was contributed by particles failure behaviours such as debonding, micro fracture, big cleavage and cutting through of particles. In order to obtain an in-depth understanding regarding the chip formation process and tool-particles interaction, Ghandehariun et al [15,16] developed a micromechanical FE model on machining Al/Al2O3 MMCs using cohesive zone element method. In their research, three main phases, namely matrix, particles, interface between matrix and particles were simulated separately.…”
Section: Introductionmentioning
confidence: 99%
“…eir study recommends optimal process parameters such as pulse on time, pulse off time, spark gap voltage, peak current, wire tension, and wire feed rate for effective machining of Al/ SiCp-MMC. Ghandehariun et al [8,9] presented a micromechanical finite element analysis developed for simulation of MMC machining. e model can simulate the behavior of all main components that distinguish the MMC, namely, the matrix, particles, and particle-matrix interface during the process, so the debonding and fracture in the particles and different scenarios of tool-particle interactions can be studied using the proposed model.…”
Section: Introductionmentioning
confidence: 99%